Hubungan Pengetahuan Dan Sikap Remaja Tentang Kesehatan Reproduksi Dengan Perilaku Seksual Pada Siswa-Siswi SMK PHI Bekasi Tahun 2016 - Dewi Rahayu; Siti Rukayah (Jurnal Persada Husada Indonesia, 2018)
Adolescence is a period of maturation period of human reproductive organs and often called puberty (Widyastuti, 2009). Sexual behavior in adolescents occurs due to lack of knowledge of adolescents to reproductive health. There is a need for preventive measures and follow-up to this problem, so that the occurrence of pregnancy out of wedlock, cervical cancer, and abortion can be prevented by changing the views and mindset of adolescents to act positively to the problem. BKKBN data in 2010, showed 51% of adolescents in Jabodetabek have premarital sex. In other words, out of 100 teens, 51 are not virgins. Apparently as many as 21% of teenagers or one in five teenagers in Indonesia have had an abortion. The purpose of this study was to determine the relationship of knowledge and adolescent attitudes about reproductive health with sexual behavior in adolescents. The type of quantitative research, with the subject of research is adolescents who attend SMK PHI Bekasi. The research process has been carried out in June 2016 in Bekasi. The population is 223 respondents and 143 respondents. The method used in sampling is qouta sampling. The results of the study found that variables related to sexual behavior are gender (p value 0.002), knowledge (p value 0.011), and attitude (p value 0.043). While the variable is not related to sexual behavior that is age (p value 0.528), Thus expected by Health Department government cooperate with Education Office to give counseling about reproductive health and sexual behavior to increase public knowledge, especially adolescent.